Smart Sensor Network-Based Autonomous Fire Extinguish Robot Using IoT - Radha, D.; Arun Kumar, M.; Telagam, Nagarjuna; Sabarimuthu, M. (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Fire explosion is among the main reasons for death in the world. The urban spaces have a lot of population, many systems have control over fire detection but not over control of fire due to lack of functionalities. The operation of the robot depends on the android application on the smartphone. It can also be communicated using Wireless fidelity technology. The motion detection technology is embedded in it, which can identify the objects or obstacles. With Arduino microcontroller and IoT technology, this robot can send emergency alerts in critical conditions, explore the compounds, and effectively check for the fire. The entire robot was contained in the sensor-based network, and if the sensors fail to detect, the robot still will operate and extinguish fire with the help of an inbuilt camera. Finally, this robot is tested for operation in automated mode and live video buffering capability.